Investigating Students’ Informal Use of AI Tools during University English Classes - Reni Apriani; Shibani Basu Dubey (MATCHA: Journal of Modern Approaches to Communication, Humanities, and Academia, 2026)
The rapid proliferation of artificial intelligence (AI) tools has transformed how university students engage with English learning, often beyond formal instructional designs. This qualitative study investigates students’ informal use of AI tools during university English classes and examines how they interpret the role of these tools in shaping their learning experiences and classroom engagement. Drawing on classroom observations and semi-structured interviews, the study explores the ways students independently integrate AI tools such as translation, paraphrasing, and generative assistance to support comprehension, participation, and task completion in real time. The findings reveal that students employ AI tools strategically to manage linguistic challenges, maintain engagement, and enhance confidence, while simultaneously negotiating concerns related to overreliance and academic norms. Students generally perceive AI as a supportive, complementary resource rather than a substitute for instruction or effort. By foregrounding informal and learner-initiated AI use, this study contributes to current discussions on AI integration in English language education, highlighting the importance of recognizing students’ everyday practices and perspectives when developing pedagogical and policy responses to AI-enhanced learning environments.